Association between Facebook Dependence and Poor Sleep Quality: A Study in a Sample of Undergraduate Students in Peru - Wolniczak Rodriguez, Isabella (2014)
Objectives: Internet can accelerate information exchange. Social networks are the most accessed especially Facebook. This kind of networks might create dependency with several negative consequences in people’s life. The aim of this study was to assess potential association between Facebook dependence and poor sleep quality. Methodology/Principal Findings: A cross sectional study was performed enrolling undergraduate students of the Universidad Peruana de Ciencias Aplicadas, Lima, Peru. The Internet Addiction Questionnaire, adapted to the Facebook case, and the Pittsburgh Sleep Quality Index, were used. A global score of 6 or greater was defined as the cutoff to determine poor sleep quality. Generalized linear model were used to determine prevalence ratios (PR) and 95% confidence intervals (95%CI). A total of 418 students were analyzed; of them, 322 (77.0%) were women, with a mean age of 20.1 (SD: 2.5) years. Facebook dependence was found in 8.6% (95% CI: 5.9%–11.3%), whereas poor sleep quality was present in 55.0% (95% CI: 50.2%–59.8%). A significant association between Facebook dependence and poor sleep quality mainly explained by daytime dysfunction was found (PR = 1.31; IC95%: 1.04–1.67) after adjusting for age, sex and years in the faculty. Conclusions: There is a relationship between Facebook dependence and poor quality of sleep. More than half of students reported poor sleep quality. Strategies to moderate the use of this social network and to improve sleep quality in this population are needed.